ROMANIAN AERONAUTICAL METEOROLOGY APPLICABLE LEGAL FRAMEWORK –BRIEFING - CATALIN POPA (Challenges of the Knowledge Society)
The purpose of this briefing is toprovide an overview of the aeronautical meteorology legal framework in Romania. In this context, the role and importance of aeronautical meteorology in international air traffic management will be underlined, with focus on the civil aviation activity in Romania. The international legal framework and modalities of implementing these rules at national level will constitute a significant part of the present study., Specific accent will be put on the national regulatory framework and structure, means of updating it, and how it responds to changing regulatory requirements.